(3WQb MOjK YHO Gddg Hf YeQ aj JQGFi GdgdGds - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM GdHZOGOi Yf GHf TgGH MOKfi SGde Hf YHO Gddg Cf YHO Gddg Hf YeQ bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd (B( (3EPG QCjJhg aUhehG hEPG QCjJehg aCaWQhG aEf Ye Ydjce aCbOQhG dg (B) s
(3BNQgG (B:s
(3UhehG dQDjJg hCaWQhG dQDjJg aEf CYei Ydjce aGbOQhG dg KdGKjf BNQ GdLRA hGdMeO ddg s
(3HChdg bQGAI hHBNQg SeGYs
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs